How Could Children’s Storybooks Promote Empathy? A Conceptual Framework Based on Developmental Psychology and Literary Theory - Kucirkova, Natalia (Frontiers in Psychology, 2019)
This conceptual paper proposes a framework for understanding the developmental mechanisms and literary characteristics that bind children’s storybooks with empathy. The article begins with a taxonomy of empathy composed of three key continuous dimensions: cognitive/emotional empathy, empathy for in-group and out-group members and empathy with positive and negative consequences. Insights from developmental psychology and literary theory form the basis for an interdisciplinary framework based on three premises: 1, book-reading can support empathy if it fosters in-group/out-group identification and minimises in-group/out-group bias; 2, identification with characters who are dissimilar from the readers is the most valuable contribution of children’s storybooks to cognitive empathy and 3, the quality of language makes children’s storybooks an exceptional, but not exclusive, empathy-building form of fictional narratives. Implications for future intervention and empirical work are provided.